Strategies for Increasing Indonesian Halal Product Exports to Russia - Putra, Muhammad Reksa Nusantara; Moenardy, Dwi Fauziansyah (Manunggal Halim Jaya, 2025)
The global halal industry continues to grow rapidly and is projected to reach more than USD 3 trillion by 2027. Indonesia, with the largest Muslim population in the world, has great potential to become a major producer and exporter of halal products. However, Indonesia's contribution to halal exports is still relatively small, only about 3% of global trade, lagging behind Malaysia, Thailand, and Brazil. Russia, as a non-Muslim country with a significant Muslim population (20–25 million people), is showing increasing demand for halal products, including food, cosmetics, pharmaceuticals, and modest fashion. This trend is driven by the growth of halal lifestyles and the adoption of halal products by non-Muslim Russian consumers who view halal products as symbols of quality and safety. This study aims to identify obstacles and formulate strategies to increase Indonesia's halal product exports to Russia. The method used is qualitative descriptive with secondary data from government agency reports, international organisations, and academic publications. The results of the study show that the main obstacles to exports include differences in halal regulations, logistical and distribution limitations, lack of promotion and branding, and limitations in the capacity of MSMEs. The recommended strategies include product innovation and differentiation tailored to Russian consumer preferences, harmonisation of halal certification, digitalisation of promotion, strengthening of the halal value chain, bilateral economic diplomacy, and empowerment of halal SME exporters.